Automatización del sistema de distribución de agua potable del esquema San Pedro de Carabayllo - distrito de Carabayllo - Osorio Urrunaga, Julio Cesar (2017)
The main objective of this thesis project was to automate the type of stations such as: Entrance chambers to the sector and reservoir of the A.H. potable water distribution system. San Pedro de Carabayllo-Carabayllo District and remote monitoring of installed equipment. The thesis project consists of 4 chapters, the first chapter is: General aspects; where it establishes the technical requirements for the viability of the present thesis project, Definition of the problem, Justification, objectives and state of the art of the thesis. The second chapter cites: Theoretical framework, where the theoretical bases necessary and attributable to the thesis are consolidated, such as the definition of the Control and instrumentation equipment to be used. In the third chapter it is mentioned: the design of the Automation, Control and Wireless Communication with 5.8 GHz radio modem in each chamber and water distribution reservoir, equipment and instrumentation selection, also the data acquisition of the pressure sensors, flow and water level and depending on them send instructions to the actuators. Likewise, its integration into SCADA through the MODBUS TCP protocol. Finally, the fourth chapter is: Result and Conclusions where the Implementation of automation and Communication systems is shown; it is in this chapter where the final result is appreciated with the complete tests of the systems where all its operation is verified according to the objectives set out in the present work. Concluding with this thesis project, it was possible to obtain in the tests of radio links in free frequency in 5.8 GHz, levels in the RSSI receiver and the SNR very optimal, it through the configuration and diagnosis software of the same manufacturer of the radio.